Preferencje polityczne a opinia publiczna - Marzec, Magdalena; Wichura, Jarosław (Political Preferences, 2011)
Political preferences and pre-election polls are interrelated. Analysis of the voice of socie- ty helps to plan rationally the future tasks and simultaneously analyze current problems, also social expectations. Although public opinion generally is perceived as acceptance or criticism of political action, but this survey and their analysis also points to a third state of indifference to politics. Often, the parties seek to reduce this third group and are communicating to a neutral or undecided voters, trying to enlarge the circle of its supporters. It is necessary to remember that public opinion is shaped by the information coming to its knowledge, and these may be subject of manipulation. It is believed that it is often manipulated by party leaders and the media. Conducive to this type of activity is the time of the election campaign, including a measure surveys of support for particular parties or candidates. Extre- mely important due to the influence of the media is the perception of fairness by the public. Analysis of the receipt of polls, assess the reliability and credibility of media sources is useful for specialists in PR and marketing franchise. The research allowed to extract some trends in the behavior of the electorate, which in view of their continuation can be very useful.